The pediatric athlete: younger athletes with sport-related concussion - Meehan, W. P.; Taylor, A. M.; Proctor, M. (Clinics in Sports Medicine, 2011)
Although much of the lay media attention surrounding sport-related concussion (SRC) focuses on professional athletes, SRC is a common injury in pediatric sports. The anatomy, biomechanics, and response to injury of the developing pediatric brain differ from those of the adult. Similarly, the neurocognitive abilities of the child are developing more rapidly than in an adult. The effects of concussive brain injury on the life of a child are different from those of an adult. This article focuses on the aspects of SRC that are specific to the younger athletes.